Long Sleep Duration and Childhood Overweight/Obesity and Body Fat - Cristina Padez (2009)
To assess the association between short sleep duration and overweight/obesity and body fat (BF) and to identify correlates of short sleep duration in a sample of Portuguese children. A cross-sectional study of children 7-9 years (n = 4511) was performed between October 2002 and June 2003. Weight, height, and skinfolds were measured, and parents filled out a questionnaire about family characteristics as well as sleep duration. The prevalence of overweight/obesity and BF (%) both decreased by long sleep duration. After adjusted for confounders, the odds ratio (OR) for overweight/obesity and sleep duration were as follows: reference > 11 h/d; 10-11 h/d, OR: 1.3; confidence interval (CI):1.26, 1.33; 9-10 h/d, OR: 1.16; CI: 1.13, 1.19; and < 9 h, OR: 3.22; Cl: 3.11, 3.32. Children whose parents' had a low educational level slept less time during each night than children whose parents' had a higher educational level; children who spent more time watching television slept less time than those who watched less television, and those children engaged in physical activity slept more time each night than sedentary children. Our results showed an inverse relationship between long sleep duration and overweight/obesity prevalence as well as with body fat, and these findings are important because sleep duration is a potentially modifiable risk factor that could be important to consider in the prevention and treatment of childhood obesity. Am. J. Hum. Biol. 21:371-376, 2009. (C) 2009 Wiley-Liss, Inc.